2022
DOI: 10.3390/ani12050611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1,25-Dihydroxyvitamin D3-Glycosides on the Farrowing Process and Piglet Vitality in a Free Farrowing System

Abstract: Vitamin D improves the reproductive efficiency in animals. This study aimed to examine the effects of 1,25-dihydroxyvitamin D3-gylcosides (1,25 vitD) on the farrowing process in sows and the vitality of their piglets. In total, 100 sows were allocated into two groups at insemination (‘1,25 vitD’ and ‘negative control’). The 1,25-vitD group received 260–300 mg/sow/day 1,25-vitD in their feed during the gestation period. Backfat thickness, fecal score, and the farrowing process was evaluated. The piglets were ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…13 Indeed, the median of liveborn piglets in our case report was 12 for the group without necrosis and 13 for the group with necrosis, while another recent study in Switzerland found a median of 15 liveborn piglets per sow. 9 However, BCS scoring is not the most reliable tool to examine changes in the body condition, because it is very subjective and only poorly correlated to backfat thickness. 23 The pathogenesis and cause of necrosis of different localisations in piglets has not yet been determined.…”
Section: Resultsmentioning
confidence: 99%
“…13 Indeed, the median of liveborn piglets in our case report was 12 for the group without necrosis and 13 for the group with necrosis, while another recent study in Switzerland found a median of 15 liveborn piglets per sow. 9 However, BCS scoring is not the most reliable tool to examine changes in the body condition, because it is very subjective and only poorly correlated to backfat thickness. 23 The pathogenesis and cause of necrosis of different localisations in piglets has not yet been determined.…”
Section: Resultsmentioning
confidence: 99%
“…However, the benefits of vitamin D go beyond that, being also involved in growth performance and immunity [ 2 ]. In this sense, several studies have assessed the impact of vitamin D supplementation on porcine health, focused mainly on gestating sows, farrowing and weaning piglets [ 9 12 , 20 25 ]. However, the effect of vitamin D supplementation in later stages of pig production and under outdoor systems has been scarcely evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, different studies have evaluated the impact of vitamin D supplementation on porcine health, showing promising results [ 9 , 12 ]. Thus, Konowalchuk et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, vitamin D supplementation involves either vitamin D 3 or 25(OH)D 3 , with the majority of research conducted on these forms of vitamin D. However, there are also studies investigating the effects of supplementation with the active form of vitamin D-1,25(OH) 2 D 3 . The addition of 260-300 mg/sow/day of 1,25(OH) 2 D 3 from plant sources increased the litter size and litter weight gain and reduced farrowing duration, weight loss of sows, and the rectal body temperature after farrowing; however, it increased the number of mummies and the number of short ruptured umbilical cords [145,146].…”
Section: Vitamin Dmentioning
confidence: 99%